FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN HUTANG PERUSAHAAN MANUFAKTUR DI BEI - Oktaviani, Klarisa; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research was conducted to determine the effect of liquidity, profitability, asset structure, and institutional ownership on debt policy of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The population of this study is 134 manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020 and selected by purposive sampling method to 72 companies as research samples. This research was using multiple linear regression analysis techniques to test the hypothesis and processed using EViews 12 software. The results of this research were liquidity, asset structure, and institutional ownership have a negative significant effect on debt policy, while profitability does not have a significant effect on debt policy.The implication of this research is the company need to increase increase the fulfillmentof their short-term liabilities in order to reduce the use of debt that is not needed by the company.